Mini Review: New Treatments in Psoriatic Arthritis. Focus on the IL-23/17 Axis - Sakkas, Lazaros I.; Zafiriou, Efterpi; Bogdanos, Dimitrios P. (Frontiers in Pharmacology, 2019)
Psoriasis, an inflammatory skin disease, and psoriatic arthritis (PsA), an inflammatory arthritis, share clinical, genetic, and pathogenic factors and may be summed as one disease, the psoriatic disease. Interleukin (IL)-17 plays a major role in the development of both psoriasis and PsA. IL-23 is important in the proliferation and maintenance of IL-17, and therefore, cytokines of the IL-23/IL-17 axis attracted much interest as therapeutic targets in psoriasis and PsA. Therapeutic agents targeting the cytokine IL-23/IL-17 axis have been proved very effective in psoriasis and PsA, some are already in the therapeutic armamentarium and others are in the development. Some agents target IL-23 and others IL-17 and include anti-IL-12/IL-23 p40 (ustekinumab, briankizumab), anti-IL-23p19 (guselkumab, tildrakizumab, risankizumab, brazikumab, mirikizumab), anti-IL-17A (secukinumab, ixekizumab), dual anti-IL-17A and anti-IL-17F (bimekizumab), or anti-IL-17 receptor (brodalumab) monoclonal antibodies. Janus tyrosine kinase(JAK) inhibitors also directly affect IL-23 and thus IL-17. After the first generation pan-JAK inhibitors have been shown efficacy (tofacitinib, baricitinib) new generation selective JAK inhibitors (filgotinib, upadacitinib) are under investigation in psoriasis and PsA.